2022
DOI: 10.1101/2022.04.14.488404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High genetic diversity in the pelagic deep-sea fauna of the Atacama Trench revealed by environmental DNA

Abstract: A current paradigm in marine biodiversity states that faunal richness decreases with depth. However, the deep-ocean ecosystem has been significantly under-sampled, hindering a complete view of its biodiversity. This situation is accentuated in ultra-deep waters, where the remote and extreme conditions unfit the traditional sampling methods. Using environmental DNA, we assessed the pelagic metazoan diversity of the Atacama Trench from the high-productive near-surface level down to ~8000 m depth. Our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The relative abundance of species observed in this study were consistent with previous research conducted using morphological and genetic approaches, extending down to the abyssopelagic zone (Kosobokova and Hirche, 2000;Vereshchaka et al, 2017;de Puelles et al, 2019;Ramıŕez-Flandes et al, 2022). In the study region off northern Chile, Calanoida and Euphausiacea dominated the zooplankton communities (Heinrich, 1973;Escribano and Hidalgo, 2000;Antezana, 2002), with Subeucalanus monachus and Euphausia mucronata adapting to hypoxic conditions in the upper 500 m (Binet, 1983;Antezana, 2002;Valdeś et al, 2007).…”
Section: Community Composition and Gene Markerssupporting
confidence: 89%
See 4 more Smart Citations
“…The relative abundance of species observed in this study were consistent with previous research conducted using morphological and genetic approaches, extending down to the abyssopelagic zone (Kosobokova and Hirche, 2000;Vereshchaka et al, 2017;de Puelles et al, 2019;Ramıŕez-Flandes et al, 2022). In the study region off northern Chile, Calanoida and Euphausiacea dominated the zooplankton communities (Heinrich, 1973;Escribano and Hidalgo, 2000;Antezana, 2002), with Subeucalanus monachus and Euphausia mucronata adapting to hypoxic conditions in the upper 500 m (Binet, 1983;Antezana, 2002;Valdeś et al, 2007).…”
Section: Community Composition and Gene Markerssupporting
confidence: 89%
“…However, both studies reached maximum depths of 1500 m and 3000 m, respectively. In our study region, analysis of environmental DNA targeting the whole metazoan community suggested a gradual increase in diversity with depth down to 8000 m (Ramıŕez-Flandes et al, 2022), although this pattern was uncertain for the zooplankton group.…”
Section: The Vertical Pattern Of Zooplankton Diversitymentioning
confidence: 69%
See 3 more Smart Citations